Oral erythema multiforme after Pfizer-BioNTech COVID-19 vaccination: a report of four cases - Massimo Petruzzi; Sara Galleggiante; Sabrina Messina; Fedora della Vella (BMC, 2022)
Abstract Background The 2019 Coronavirus disease (Covid-19) has affected thousands of people worldwide. To date, vaccines appear to be the only method to prevent and reduce mortality. Four vaccinations have been outwardly approved by European Medicine Agency (EMA) in Europe: BNT162b2 (Comirnaty-BioNTech/Pfizer), mRNA-1273 (Spikevax-Moderna), ChAdOx1 (VaxzevriaAstrazeneca), and Ad26.COV2-S (Janssen-Johnson&Johnson). After vaccination, local and systemic adverse effects can occur. Cutaneous reactions like urticaria, local injection site pain, morbilliform rash have been documented after vaccination. Cases presentation We report four cases of oral erythema multiforme flare arising after BNT162b2 vaccination administration. All the patients denied previous erythema-like and herpetic manifestations history. Two of the reported cases (number 1 and 2) presented with both oral and cutaneous lesions, while cases 3 and 4 showed only oral manifestations. Three of the cases presented the erythema after the first vaccination dosage administration, only one case reported lesions after the second vaccination dosage administration. All the cases were treated with prednisone via oral administration and topical 0.05% clobetasol ointment. Conclusions The present reports represent some of the few cases of erythema multiforme occurring as a side effect of the BNT162b2 COVID-19 vaccination. The causal role of the vaccine for the erythema multiforme has not been proven yet; nevertheless, it is not uncommon for medications to trigger this disease. The vaccine could surface a silent herpes virus infection, which would induce the erythema multiforme instead.